Childhood obesity: Aetiology, comorbidities, and treatment (2019)
Obesity is currently considered a global epidemic, and its implications in mortality and morbidity in a paediatric patient and in adulthood are increasingly important. The objective of this article is to review in detail the definition of obesity according to age group, and, in turn, the epidemiology of this entity worldwide and in South America. Available evidence about pathophysiology and, additionally, associated comorbidities are reported in some of the most important and clinically relevant body systems. The recommendations on pharmacological and nonpharmacological management through changes in lifestyle and relevant aspects of bariatric surgery in the paediatric population are also described.